The Action to Create a Sufficiency Community of Moken Ethnic Group, Koh Lao, Ranong Province - Changkid, Pariwat (Area Based Development Research Journal, 2019)
This research aims to create a sufficiency community of the Moken ethnic group in Koh Lao, Ranong province. It is a participatory action research consisting of 5 activities: 1) implementing waste management system in the community, 2) developing a creative space/place for communal activities, 3) rearranging homes for healthy/hygienic living, 4) providing community welfare, and 5) creating social learning process. Data are collected by participation and non-participation observation, in-depth interviews, focus group discussions, and community meetings. The participants are 30 households in the Moken community. The action to create sufficiency in the Moken community consists of 7 steps: 1) understanding 2) community analysis 3) planning 4) public relations 5) implementation 6) evaluation and 7) improvement/development. The research finds that the arranged activities to build a sufficient community result in the Moken’s understanding and positive attitude towards living on the path of self-sufficiency. While desirable behavior of sufficiency living is found low, the satisfaction on activities is at the highest level. The implementation of this approach can change the way of life and adjust some unwanted behaviors in daily life. It also helps the community to understand the value of teamwork. The results of this study imply the possibility for implementation of Sufficiency Economy Philosophy to the marginalized community because it can provide lifelong security for these people.